2018
DOI: 10.1097/md.0000000000013816
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect between continuous infusion and intermittent bolus of rocuronium for intraoperative neurophysiologic monitoring of neurointervention under general anesthesia

Abstract: Background:Medical researchers have been reluctant to use neuromuscular blocking drugs (NMBD) during the use of intraoperative motor evoked potential (MEP) monitoring despite the possibility of patient movement. In this study, we compared the effects of no NMBD and continuous rocuronium infusion on the incidence of patient involuntary movement and MEP monitoring.Methods:In this study, 80 patients who underwent neuro intervention with MEP monitoring were randomly assigned into 2 groups. After an anesthetic indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In their study, no spontaneous movement or spontaneous breathing events were reported in any of the 276 patients who underwent aneurysm clipping with no NMB. In the study by Ko et al [ 19 ], propofol (effect-site concentration, 2–5 μg/mL) and remifentanil (2–4 ng/mL) were infused via a TCI pump for anesthesia maintenance. The incidence of spontaneous movement and respiration was 30.0% (12/40) and 15.0% (6/40), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, no spontaneous movement or spontaneous breathing events were reported in any of the 276 patients who underwent aneurysm clipping with no NMB. In the study by Ko et al [ 19 ], propofol (effect-site concentration, 2–5 μg/mL) and remifentanil (2–4 ng/mL) were infused via a TCI pump for anesthesia maintenance. The incidence of spontaneous movement and respiration was 30.0% (12/40) and 15.0% (6/40), respectively.…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of intraoperative spontaneous movement during motor-evoked potential monitoring in patients undergoing neurosurgery. CI, confidence interval, [ 10 , 12 , 13 , 17 , 19 , 20 ]. …”
Section: Figurementioning
confidence: 99%
“…Some studies have shown that partial neuromuscular blockade can provide the right monitoring conditions for neurophysiological monitoring and improve the safety of anaesthesia and surgery. 11 , 12 Although the existing research results have shown the relationship between the degree of muscle relaxation and MEP amplitudes, most of the clinical anaesthesia in China does not have the requirement of monitoring the degree of muscle relaxation. Therefore, the purpose of this study was to identify an optimal muscle relaxant dose to provide useful reference information for spinal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ko et al, continuous infusion of rocuronium effectively inhibited unexpected intraoperative body movement and spontaneous breathing of the patient while enabling MEP monitoring. 12 Therefore, it is essential to identify an appropriate maintenance dose of a muscle relaxant that ensures smooth progression of the operation without interfering with neurophysiological monitoring for spinal surgery.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The ideal muscle relaxation for robotic thyroid surgery should meet the requirements of surgical operation, avoid affecting the operation, and not interfere with IONM. Studies have shown that appropriate neuromuscular blockade can provide appropriate neurophysiological monitoring conditions and improve the safety of anesthesia and surgery ( 24 , 31 ). This indicates that our experiment has clinical significance.…”
Section: Discussionmentioning
confidence: 99%